PENGEMBANGAN VIDEO PEMBELAJARAN K3 PELAJARAN PDTO KELAS X TKR DI SMK MUHAMMADIYAH PIYUNGAN - Indra Kusumah; Nurcholish Arifin H; Dianna Ratnawati (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to: (1) produce K3 learning videos for students of class X Automotive Engineering at SMK Muhammdiyah Piyungan Bantul; (2) Knowing the feasibility of the occupational safety and health learning videos produced to be used as teaching materials for class X Automotive Engineering students at SMK Muhammdiyah Piyungan Bantul; Research and development, which is the development of K3 learning videos for PDTO subjects at SMK Muhammadiyah Pyungan Bantul, uses the modified Four-D method by Riski and Linuhung. Feasibility data collection using interviews, questionnaires and documentation. This study involved material experts, media experts, and students to get an assessment and response to the feasibility of learning videos. The data analysis technique used is quantitative descriptive analysis. The results of the study indicate that the process of developing a learning video on Occupational Health and Safety is based on the definition stage , the design stage or initial information collection, the development stage , and the dissemination stage . The results of the assessment of the feasibility level of learning videos carried out by material experts obtained a percentage of 86% with a very decent category. The results of the media expert's assessment obtained a percentage of 81% with a decent category. And the results of the assessment of the small class trial obtained a percentage of 85% in the appropriate category and the results of the large class trial obtained a percentage of 80% in the feasible category. The research shows that the occupational safety and health learning videos are appropriate to be used in the learning process at SMK Muhammdiyah Piyungan Bantul.